Shifting Perception of Riddles: from Reflection in Traditional Riddles to Metaphorical Washing-out of the Term in Mass Media. - Kensminienė, Aelita (Tautosakos darbai, 2017)
The article focuses on perception of riddles – both as a term and as a folklore genre – and its development. The article consists of two parts. The first one deals with traditional usage, starting with reflection of riddles in the riddles themselves, with words related to riddles or the process of riddling, and going on to the explanations of riddle nature and purpose encountered in folk legends and folktales describing various situations of riddling. The second part mostly dwells on materials collected by the author in the course of approximately three years from daily environment, social media (Facebook), and internet publications, focusing on the modern usage of riddles or phenomena akin to them.Traditionally, the word riddle (mįslė in Lithuanian) tends to be used in its direct sense, i.e. as denomination of the genre. Whenever riddles discuss riddling, they mainly emphasize the intellectual nature of this genre, describing riddling as an intense and solemn occupation, aimed at demonstrating one’s knowledge, sense and creativity, and earning reward or punishment as a result. In terms of language, particularly dialects, the spheres of riddling and thinking, remembering, guessing, and speculation are not strictly separate. The situations of riddling in folk narratives are loaded with various intimidations, taboos and myths. It is reasonable to assume that this process was perceived as dangerous and threatening, while riddles as a genre must have been attributed to the chthonic sphere. Interestingly enough, in the Lithuanian variants of the tale AT 812, it is typically a small child or a baby who guesses the answer to the devil’s riddle. The traditional worldview relates the baby with the chthonic sphere, since allegedly it has recently emerged from there.Although classical riddles are rare in contemporary usage, most of their functions and topics survive in transformed shape. Various intellectual quizzes organized at bars and cafes, by radio and TV shows, and internet competitions fulfill the function of demonstrating knowledge and resourcefulness. Cases of riddling that most resemble traditional usage take place virtually – on Facebook. Modern journalists seeking to capture the readers’ interest are especially prone to using the term riddle in the titles of their articles, although mainly indirectly – implying that subject in question is obscure, unclear, and requires investigation. Admittedly, although such titles most frequently have negative connotations and besides, certain metaphorical “washing-out” of the term is obvious, in most cases they do not wander far away from the spheres that traditionally fell into their “range of interest”. Such cases of usage go back to their roots even in terms of form, since the earliest recorded riddles used to adopt the dialogical shape of questions and answers.
Keywords: -